The effects of dietary cation-anion difference and dietary buffer for lactating dairy cattle under mild heat stress with night cooling - C.A. Bertens; C. Stoffel; M.B. Crombie; P. Vahmani; G.B. Penner (Journal of Dairy Science)
ABSTRACT: The objective of this study was to investigate the interactive effect of DCAD and dietary buffer supply on DMI, ruminal fermentation, milk and milk component yields, and gastrointestinal tract (GIT) permeability in lactating dairy cattle exposed to mild heat stress. A total of 16 lactating Holstein cows, including 8 ruminally cannulated primiparous (80 ± 19.2 DIM) and 8 noncannulated multiparous (136 ± 38.8 DIM) cows, were housed in a tiestall barn programmed to maintain a temperature-humidity index (THI) between 68 and 72 from 0600 h to 1600 h followed by natural night cooling. The experimental design was a replicated 4 × 4 Latin rectangle (21-d periods) with a 2 × 2 factorial treatment arrangement. Diets contained a low DCAD (LD; 17.5 mEq/100g of DM) or high DCAD (HD; 39.6 mEq/100g of DM) adjusted using NH4Cl and Na-acetate, with low (LB; 0% CaMg(CO3)2) or high buffer (HB; 1% CaMg(CO3)2). In addition to measurement of feed intake, ruminal fermentation, and milk and milk component yields, a ruminal dose of Cr-EDTA and an abomasal dose of Co-EDTA were used to evaluate total and postruminal gastrointestinal tract permeability, respectively. Treatments had no effect on DMI, ruminal short-chain fatty acid concentrations, or ruminal pH. Feeding HD improved blood acid-base balance, increased urine volume by 4 ± 1.5 kg/d, and increased milk fat by 0.14 ± 0.044 percentage units and milk fat yield by 36.5 ± 16.71 g/d. HB reduced milk fat percentage by 0.11 ± 0.044 percentage units and had no effect on milk fat yield. The HB treatments reduced urinary excretion of Co by 27% and tended to reduce urinary Cr excretion by 10%. Across all treatments, 72% of the Cr recovery was represented by Co suggesting that much of the permeability responses were postruminal during mild heat stress. Overall, increasing DCAD through greater Na supply during mild heat stress improved blood acid-base balance and may increase milk fat yield. Dietary inclusion of CaMg(CO3)2 improved postruminal GIT barrier function despite a lack of low ruminal pH. Because there appeared to be a limited interactive effect between DCAD and buffer, increased DCAD and the provision of buffer seem to independently influence physiological and performance responses in lactating dairy cows exposed to mild heat stress with night cooling.